Особливості рецепції роману М. Сервантеса “Дон Кіхот” в українській та англійській прозі 10–20-х років XX ст. - Школа, Ірина Вікторівна (Київський національний університет імені Тараса Шевченка Міністерства освіти і науки, молоді та спорту України, 2012)
Дисертацію присвячено рецепції роману “Дон Кіхот” в українській та англійській прозі 10–20-х років ХХ ст. Матеріалом дослідження є “Історія Якимового будинку” В. Винниченка, “Подорож ученого доктора Леонардо і його майбутньої коханки прекрасної Альчести у Слобожанську Швайцарію” М. Йогансена, “Санаторійна зона”, “Сентиментальна історія” М. Хвильового, “Золоті лисенята” Ю. Шпола, “Байгород” Ю. Яновського, “Зулейка Добсон” М. Бірбома, “Орландо” В. Вулф, “Улісс” Дж. Джойса, “Повернення Дон Кіхота” та “Перелітний шинок” Г.-К. Честертона. У дисертації вперше в українському літературознавстві системно досліджено та розкрито специфіку інтерпретації роману М. Сервантеса в літературно-критичному дискурсі України та Англії 10–20-х років ХХ ст., висвітлено ступінь традиційності й новаторства у творенні образу Дон Кіхота. Окреслено чинники, що зумовлюють особливості рецепції в кожній із національних літератур, уточнено етапи сприйняття твору іспанського письменника митцями і науковцями з часу першої публікації “Дон Кіхота” і до наших днів, розширено відомості про специфіку англо-іспанської літературної комунікації на основі дослідження зарубіжних наукових джерел.
The present dissertation is devoted to the reception of the Cervantes’ novel “Don Quixote” in the Ukrainian and British prose of 1910s – 1920s. Typological comparison of Cervantes’ novel local receptions in the prose of Ukrainian (V. Vynnychenko, M. Johansen, M. Khvylyovy, J. Shpol, J. Yanovsky) and English writers (M. Beerbom, V. Woolf, J. Joyce and G.-K. Chesterton) allowed to characterize the psychological and philosophical and religious context of its interpretations based on socio-historical atmosphere of 1910s – 1920s. It was found that traditional plot, reconsidered by Ukrainian and English writers, was free from the receptive stereotypes of past centuries. The understanding of “Don Quixote” semantic features became deeper, due to the structural reorientation of non-essential characteristics. It situation closely connected, firstly, with total intellectualization of literature, and secondly, with modernists author's approach in the interpretation of a traditional plot. The author shows that, the main difference of Ukrainian quixotic discourses is the complete lack of the religious context of the interpretation of Don Quixote’s image. The reason of this is the historical situation in the country which activated a primarily psychological component of the traditional material. It is proved that Cervantes’ novel was perceived by the writers as a unique philosophical and psychological, and also, in the case of V. Woolf and G.-K. Chesterton, a philosophical and religious fiction matrix, which can reproduce the underlying trends of the epoch. The plot about the noble knight from Lamancha became a kind of ethical and aesthetic complex. Ukrainian, English and Spanish cross-cultural communication took place in its space. It was a kind of dialogue between auto-image and heteroimage, where Cervantes’ work and the image of Don Quixote in particular, embodies the image of the latter. The elements of carnival poetics and discourse of theatricality as important components of the reception of “Don Quixote” by M. Cervantes are characterized. They are investigated as the essential conceptual basis of the source text and works by V. Woolf, M. Jlohansen, M. Khvylyovy and G. -K. Chesterton and demonstrate not only the reception of the Spanish novel on the world outlook level, but also the typological common features and similarities of attitude towards life. The comparative analysis of the Ukrainian and English texts, in the context of different forms of reception of the novel by Spanish writer revealed typological coincidences and differences in rethinking the traditional image of Don Quixote. The work determines the chivalric discourse as a component of “Don Quixote” reception and considers new features in Dulcinea’s and Sancho Panza’s images reinterpretation. Therefore, typological comparison of the examples of Ukrainian and English prose of 1910s – 1920s, where different forms of the reception of the novel “Don Quixote” (modification of images, numerous borrowings, allusions, reminiscences, etc.) can be found, was conducted. It proved that borrowing and rethinking of Cervantes’ novel is the complicated and multidimensional process, existing according to the laws of interliterary motivation of learning different national experience and characterized by aspiration, using a binary opposition between auto-image and heteroimage to reveal the peculiarities of their own mental auto-image and indicates the common direction of the development of Ukrainian and English prose of noted period.
Keywords: рецепція; міжкультурна комунікація; традиційний образ; сюжет; карнавальне мислення; національна ідентичність; reception; traditional plot; prose; the image of Don Quixote communication; cross-cultural; quixotic discourse; quixoti; carnival thinking